2022
DOI: 10.1021/jacs.2c03832
|View full text |Cite
|
Sign up to set email alerts
|

Precision Navigation of Hepatic Ischemia–Reperfusion Injury Guided by Lysosomal Viscosity-Activatable NIR-II Fluorescence

Abstract: Hepatic ischemia–reperfusion injury (HIRI) is responsible for postoperative liver dysfunction and liver failure. Precise and rapid navigation of HIRI lesions is critical for early warning and timely development of pretreatment plans. Available methods for assaying liver injury fail to provide the exact location of lesions in real time intraoperatively. HIRI is intimately associated with oxidative stress which impairs lysosomal degradative function, leading to significant changes in lysosomal viscosity. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
72
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(74 citation statements)
references
References 65 publications
1
72
0
1
Order By: Relevance
“…In addition, it has been reported that lysosomal membranes are vulnerable to insults such as ischemia and reperfusion injury and oxidative stress. 32 Moreover, SerpinB3 is a known inhibitor of cathepsin L, a cysteine protease that relocalizes to the cytoplasm after disruption of the lysosomal membrane 33 and recent data demonstrated the role of SerpinB3 in protecting cathepsin L-mediated cell death after lysosomal membrane permeability. 34 In conclusion, molecular processes occurring during hepatic I/R are diverse, and continuously include new and complex mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that lysosomal membranes are vulnerable to insults such as ischemia and reperfusion injury and oxidative stress. 32 Moreover, SerpinB3 is a known inhibitor of cathepsin L, a cysteine protease that relocalizes to the cytoplasm after disruption of the lysosomal membrane 33 and recent data demonstrated the role of SerpinB3 in protecting cathepsin L-mediated cell death after lysosomal membrane permeability. 34 In conclusion, molecular processes occurring during hepatic I/R are diverse, and continuously include new and complex mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, the HIRI mouse model was established by following the previouslyreported method. 23 And the experimental protocol is shown in Fig. S22A (ESI †).…”
mentioning
confidence: 99%
“…Near-infrared II fluorescence imaging and optoacoustic (photoacoustic) imaging are advantageously conducive to detecting and imaging in situ biomarkers. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] In NIR-II fluorescence imaging, the relatively long wavelength (with emission in the 900-1700 nm region) could ensure much higher imaging resolution, since autofluorescence and light scattering in biological samples in the long wavelength range are abated to a large extent. [7][8][9][10][11][12][13][14][15][16][17] In optoacoustic imaging, ultrasound waves that are generated by photoexciting contrast agents/probes are collected as reported signals which are irrelevant to photon scattering, hence images of high resolution can be obtained with relatively large penetration depth.…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] In NIR-II fluorescence imaging, the relatively long wavelength (with emission in the 900-1700 nm region) could ensure much higher imaging resolution, since autofluorescence and light scattering in biological samples in the long wavelength range are abated to a large extent. [7][8][9][10][11][12][13][14][15][16][17] In optoacoustic imaging, ultrasound waves that are generated by photoexciting contrast agents/probes are collected as reported signals which are irrelevant to photon scattering, hence images of high resolution can be obtained with relatively large penetration depth. [18][19][20][21][22][23] Multispectral optoacoustic tomography (MSOT) imaging, as a functional optoacoustic imaging method, can single out the optoacoustic signals contributed by a specific contrast agent/probe with the sample being irradiated by multiple-wavelength lasers and the gathered data being processed with spectral unmixing algorithms.…”
mentioning
confidence: 99%